Ponovno branje Epiloga k Vinjetam - Kramberger, Igor (Slavistična revija, 2010)
The author provides an interpretation of a fragment from Cankar's Epilogue to his Vinjete, which has been now understood as its satirical part. By making connection with the notion of the literary field, the fragment is explained as Cankar's suggestion to Sshwentner, what he should do in order to become an important publisher. If he re-published older works, he would ensure the appropriate place for the new as well as for the future literary works. By limiting the analysis to a fragment rather than treating the whole text, the author broadened the perspectives from which literary history is studies within empirical and systemic literary criticism.
Keywords: Cankar, Ivan, 1876-1918; Cankar, Ivan: Vinjete; kratka proza; moderna; Moderna Therapeutics; Schwentner, Lavoslav, 1865-1952; Slovene literature; slovenska književnost; slovenski pisatelji; založniki